Experimental assessment of out‐of‐field dose components in high energy electron beams used in external beam radiotherapy - Alabdoaburas, Mohamad M. (J Appl Clin Med Phys, 2015)
The purpose of this work was to experimentally investigate the out‐of‐field dose in a water phantom, with several high energy electron beams used in external beam radiotherapy (RT). The study was carried out for 6, 9, 12, and 18 MeV electron beams, on three different linear accelerators, each equipped with a specific applicator. Measurements were performed in a water phantom, at different depths, for different applicator sizes, and off‐axis distances up to 70 cm from beam central axis (CAX). Thermoluminescent powder dosimeters (TLD‐700) were used. For given cases, TLD measurements were compared to EBT3 films and parallel‐plane ionization chamber measurements. Also, out‐of‐field doses at 10 cm depth, with and without applicator, were evaluated. With the Siemens applicators, a peak dose appears at about 12–15 cm out of the field edge, at 1 cm depth, for all field sizes and energies. For the Siemens Primus, with a [Formula: see text] applicator, this peak reaches 2.3%, 1%, 0.9% and 1.3% of the maximum central axis dose (Dmax) for 6, 9, 12 and 18 MeV electron beams, respectively. For the Siemens Oncor, with a [Formula: see text] applicator, this peak dose reaches 0.8%, 1%, 1.4%, and 1.6% of Dmax for 6, 9, 12, and 14 MeV, respectively, and these values increase with applicator size. For the Varian 2300C/D, the doses at 12.5 cm out of the field edge are 0.3%, 0.6%, 0.5%, and 1.1% of Dmax for 6, 9, 12, and 18 MeV, respectively, and increase with applicator size. No peak dose is evidenced for the Varian applicator for these energies. In summary, the out‐of‐field dose from electron beams increases with the beam energy and the applicator size, and decreases with the distance from the beam central axis and the depth in water. It also considerably depends on the applicator types. Our results can be of interest for the dose estimations delivered in healthy tissues outside the treatment field for the RT patient, as well as in studies exploring RT long‐term effects. PACS number(s): 87.53.Bn, 87.56.bd, 87.56.J‐